Analisis Kebutuhan Media Pembelajaran Anak TK di Sumba Barat Daya - Bessu, Lidia Vera (Varied Knowledge Journal, 2025)
This research aims to analyze the need for learning media for Kingdegarten (TK) children in Southwest Sumba Regency, East Nusa Tenggara. Learning media plays an important role in improving the quality of early childhood education, so this research is expected to provide insight into the types of media needed, the challenges faced, and solutions that ca be implemented. Through a qualitative approach using interview and observation methods, this research found that althogh many kindergartens have implemented several traditional learning media, there are still shortcomings in terms of access to more interactive and technology-based learning media. Therefor, development and media distribution learning right on target is indispensable to support Develpoment cognitive, affective, and child psychomotor chidren in Sumba Southwest.